POETRY IS A MIRROR OF HAPPINESS - DILAFRUZ JABBOROVA; MUYASSAR MUSTAFOYEVA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article discusses the role of poetry in depicting the image of self-aware people, a leading principle in the 80s short stories.